A Longitudinal Study of Emotion Regulation, Emotion Lability‐Negativity, and Internalizing Symptomatology in Maltreated and Nonmaltreated Children. Issue 2 (3rd October 2012) - Kim‐Spoon, Jungmeen; Cicchetti, Dante; Rogosch, Fred A.
<x xml:space="preserve">Abstract</x> The longitudinal contributions of emotion regulation and emotion lability‐negativity to internalizing symptomatology were examined in a low‐income sample (171 maltreated and 151 nonmaltreated children, from age 7 to 10 years). Latent difference score models indicated that for both maltreated and nonmaltreated children, emotion regulation was a mediator between emotion lability‐negativity and internalizing symptomatology, whereas emotion lability‐negativity was not a mediator between emotion regulation and internalizing symptomatology. Early maltreatment was associated with high emotion lability‐negativity (age 7) that contributed to poor emotion regulation (age 8), which in turn was predictive of increases in internalizing symptomatology (from age 8 to 9). The results imply important roles of emotion regulation in the development of internalizing symptomatology, especially for children with high emotion lability‐negativity.